PENGARUH AKUNTANSI BERBASIS SAK EMKM, KUALITAS SUMBER DAYA MANUSIA, DAN KARAKTERISTIK USAHA TERHADAP KUALITAS LAPORAN KEUANGAN - Cahyani, Afida Dwi; Mulyani, Sri Mulyani; Budiman, Nita Andriyani (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The aim of this study was to find out the effect of SAK EMKM-based accounting, education level, accounting knowledge, lenght of bussines, and size of bussines on the quality of financial report. This study was a quantitative research using primary data types by questionnaires and measured using a Likert scale. The population of this research was all UMKM businessman in Pati Regency. The sampling technique used purposive sampling, as many as 43 MSME actors. The data analysis technique in this study uses multiple linear regression analysis with the help of SPSS version 23. The results of this study indicate that accounting knowledge has a positive effect on the quality of financial reports, while SAK EMKM-based accounting, education level, length of business, and size of business have no effect on quality of financial reports.